Ode to a lost icon, David Jones. Issue 2 (April 2022) - Ravelli, Louise
The dramatic impact of online shopping on 'bricks and mortar' retail is well known, and large, well-established department stores have been no exception. This article provides a case study of one department store, 'David Jones' in Sydney, which has been a long-term feature of the retail landscape in Australia. This store's embodiment of glamour and service has come to define David Jones as an institution, but the affordances of the conventional department store have been challenged in the current environment, disrupting a once-stable social practice. Using Spatial Discourse Analysis and the concepts of discourse, design, production and distribution, the article compares the key attributes which defined David Jones in the past, how those attributes have been disrupted, how the store has responded to those disruptions, and why its responses seem less effective than those of some of its competitors.